Geographical Indication & Gastro-Diplomacy as Nation Branding - Mayana, Ranti Fauza; Santika, Tisni (Lentera Hukum, 2024)
In response to the success of “Eat, Pray and Love” in 2010, Paul Rockower highlighted Indonesia's great opportunity to carry out a robust culinary-based public diplomacy campaign. As a specialist in culinary diplomacy, he noted this to be the key to help Indonesia to enhance its longstanding reputation as an exotic culinary locale. This paper aims to analyze the opportunities and challenges in implementing geographical indication (GI) as part of gastrodiplomacy strategies, and how it impacts the strengthening of Indonesia’s national branding. This paper finds that, to effectively integrate GI protection into the gastrodiplomacy strategy, it is necessary to take strategic steps that follow the characteristics of GI as IP with a collective dimension—through a series of collective action stages, using an institutional approach. Although the collaboration is time-consuming, involving different stakeholders (such as local producers, organizations, research institutions, the local and central government, private sectors, communities, and other institutions) is the key to integrating GI protection into gastrodiplomacy strategies.KEYWORDS: Gastrodiplomacy, Geographical Indication, Nation Branding.